Resveratrol improves glycemic control in insulin-treated diabetic rats: participation of the hepatic territory. Issue 1 (December 2016) - Yonamine, Caio; Pinheiro-Machado, Erika; Michalani, Maria; Freitas, Helayne; Okamoto, Maristela; Corrêa-Giannella, Maria; Machado, Ubiratan
Abstract Background Resveratrol is a natural polyphenol that has been proposed to improve glycemic control in diabetes, by mechanisms that involve improvement in insulin secretion and activity. In type 1 diabetes (T1D), in which insulin therapy is obligatory, resveratrol treatment has never been investigated. The present study aimed to evaluate resveratrol as an adjunctive agent to insulin therapy in a T1D-like experimental model. Methods Rats were rendered diabetic by streptozotocin (STZ) treatment. Twenty days later, four groups of animals were studied: non-diabetic (ND); diabetic treated with placebo (DP); diabetic treated with insulin (DI) and diabetic treated with insulin plus resveratrol (DIR). After 30 days of treatment, 24-hour urine was collected; then, blood, soleus muscle, proximal small intestine, renal cortex and liver were sampled. Specific glucose transporter proteins were analyzed (Western blotting) in each territory of interest. Solute carrier family 2 member 2 (Slc2a2 ), phosphoenolpyruvate carboxykinase (Pck1 ) and glucose-6-phosphatase catalytic subunit (G6pc ) mRNAs (qPCR), glycogen storage and sirtuin 1 (SIRT1) activity were analyzed in liver. Results Diabetes induction increased blood glucose, plasma fructosamine concentrations, and glycosuria. Insulin therapy partially recovered the glycemic control; however, resveratrol as adjunctive therapy additionally improved glycemic control and restored plasma fructosamine concentration to values of non-diabetic rats. Resveratrol did not alter the expression of the glucose transporters GLUT2 and SGLT1 in the intestine, GLUT2 and SGLT2 in kidney and GLUT4 in soleus, suggesting that fluxes of glucose in these territories were unaltered. Differently, in liver, resveratrol promoted a reduction inSlc2a2, Pck1, andG6pc mRNAs, as well as in GLUT2 protein (P  < 0.05, DIR vs. DI); besides, it increased (P  < 0.01, DIR vs. DI) the hepatic glycogen content, and SIRT1 protein. Conclusions Resveratrol is able to improve glycemic control in insulin-treated T1D-like rats. This effect seems not to involve changes in glucose fluxes in the small intestine, renal proximal tubule, and soleus skeletal muscle; but to be related to several changes in the liver, where downregulation ofSlc2a2 /GLUT2, Pck1, andG6pc expression was observed, favoring reduction of glucose production and efflux. Besides, resveratrol increased SIRT1 nuclear protein content in liver, which may be related to the observed gene expression regulations.